'Humanitarian borderwork': Identifying tensions between humanitarianism and securitization for government contracted NGOs working with adult and unaccompanied minor asylum seekers in Australia. (May 2019) - Gerard, Alison; Weber, Leanne
This article challenges the common assumption that non-government organizations (NGOs) are 'natural allies' to asylum seekers in transforming borders from below by examining theories of humanitarianism within the context of securitization. Our article examines the theoretical and policy implications of the 'humanitarian borderwork' of NGOs, defined as practices that contain a security logic that construct, shift and erase internal and external borders. Our case study explores the involvement of government contracted NGOs in the delivery of services to adult and unaccompanied minor asylum seekers on the community detention and release programme in Australia. Documentary analysis of policy and contractual arrangements informing the establishment of community detention and release is supplemented by key informant interviews with government officials and service providers. We analyse the contradictory tensions that exist between humanitarian objectives that seek to 'transform borders from below' and governmental security imperatives that tend to co-opt agencies and limit their ability to achieve humanitarian aims. Based on the case study presented, we illustrate how the 'humanitarian borderwork' of NGOs can shape the translation of government power and contribute to the government agenda of border securitization.